Passionately Educating Basic English to Generasi Pengubah Kindergarten Students - Deyani, Christine; Patricia, Adinda Wulan; Ferstephanie, Jenni; Purba, Sharon Maria Magdalena; Pratiwi, Theodesia Lady (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2021)
English took a crucial part in the world. It has become an international language all over the world, and everyone should learn English. English for Young Learners should start right away, as soon as possible. The implementation aims to achieve students who can learn English well since they are in kindergarten and the other aims are the authors can become a good teacher with good teaching method for the students. The place for the teaching is TK Generasi Pengubah. The participants for the implementation are 17 students. The team conducted the meeting four times and each meeting have different materials for the students. As a result of the implementation, the team are welcomed by the students at that school. The students do enjoy every meeting of the lesson and even ask the members to come again to teach them